A Revıew Of Factors Around The Emergence Of Born Global Entrepreneurs In The SADC Regıon. - Muchazoreka nyamugama; Abubaker Qutieshat (Cita Konsultindo Research Center, 2024)
The growth and mainstreaming of internet access and usage within commercial spaces has been pervasive throughout the globe. It has facilitated the emergence of the phenomenon of born global firms. However research and data collection on the phenomenon has not been equitable, with African economies, mostly being overlooked in early studies and compilations of data. One of the paper’s intentions is to bridge this gap by reviewing studies of Born Global companies and entrepreneurs within the context of emerging markets and Southern African Developed Community (SADC) in particular. Specifically, the Born Global entrepreneur's knowledge and behaviors required to start a Born Global firm in emerging markets. It examines factors within the political economy related to the growth of Born Globals in the global market place. It analyses the potential for born global entrepreneurs and firms to effectively address the challenges of youth unemployment . Results reflect common entrepreneurial traits and threads in both developed and emerging markets. Emerging markets however face greater challenges with poor infrastructure creating less of an enabling environment riddled with poor leadership, corruption and misaligned priorities. Despite this one can conclude that Born Globals have the potential to solve the unemployment problem in SADC